Training to improve attentional dysfunction in children and adolescents with Asperger Syndrome through direct cognitive stimulation. - Bravo-Alvarez, María-Ángeles; Frontera-Sancho, María (Anales de Psicología / Annals of Psychology, 2016)
This research analyzes the generalization ability of learning in children and adolescents with Asperger Syndrome to attentional cognitive aspects with different demands on exercised through the use of a direct cognitive stimulation program. The sample consisted of 15 cases with Asperger between 7 and 15 years (M = 12, SD = 2.7) with attentional difficulties, measured by psychometric orientation instruments, to which an attention training program was implemented to two hours per week for six consecutive months. The results of the pretest-posttest analysis showed statistically significant differences in all attentional subsystems. Selective attention differences are moderate in variables related to processing speed, in sustained attention the reaction time significantly decreased (moderate magnitude of the difference) and increased the successes reducing errors (both with a large magnitude difference) . In alternating attention, a greater number of successes were observed and in split attention higher levels of total responses (both moderate magnitude) were obtained. It is concluded that the attentional performance in the cases analyzed improvement after applying a cognitive training program specifically being able to generalize learning psychometric measures.